TWIN‐WING DESIGN OPTIONS USED FOR UNMANNED AERIAL VEHICLES TO ACHIEVE HIGH ALTITUDES AT LOW SPEEDS - McAndrew, Ian R.; Vishnevskaya,Assistant Prof. Elena; Carruthers, Dr. Andrew (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
The paper addresses the aerodynamic performance of twin‐wing aircraft (biplanes) that are remotely piloted. While twin wing aircraft are acknowledged as to having greater maneuverability than monoplanes, they have inherent disadvantages based on the set position of the upper wing to meet piloting needs which induces significant levels of drag from the struts that link the upper and lower wings together. In this research, the aerodynamics of the wing position in relationship to the lower wing are analyzed with Computational Fluid Mechanics/Dynamics and simulation models. It will show that modern material can eliminate the strut drag and allow for greater lift at lower speeds. This proposed design is capable of achieving much higher altitudes with low speeds to offer advanced applications for Unmanned Aerial Vehicles, UAVs.